A thermo-reversible furfuryl poly(thioether)-b-polysiloxane-b-furfuryl poly(thioether) triblock copolymer as a promising material for high dielectric applications. Issue 10 (15th February 2022) - Feng, Zhanbin; Guo, Jiafang; Cao, Xiaohan; Feng, Guofei; Chen, Zheqi; Zhang, Xing-Hong
Abstract : The key to achieving homogenous dielectric elastomers (DEs) with broader application prospects is obtaining a high dielectric constant ( ε ′), excellent mechanical properties, and self-healing abilities. Abstract : The key to achieving homogenous dielectric elastomers (DEs) with broader application prospects is obtaining a high dielectric constant ( ε ′), excellent mechanical properties, and self-healing abilities. Herein, we report thermo-reversible furfuryl poly(thioether)- b -polysiloxane- b -furfuryl poly(thioether) triblock copolymer based homogenous DEs with tunable dielectric and mechanical performances. The triblock copolymer (PSiFGE) is synthesized via the silicon alkoxide catalyzed ring-opening polymerization (ROP) of furfuryl glycidyl ether (FGE) and carbonyl sulfide (COS). The Diels–Alder (DA) reaction is then realized after the incorporation of bismaleimide (BMI), and the thermo-reversible homogenous DE (PSiFGE-BMI) is obtained. The introduction of DA bonds endows PSiFGE-BMI with a thermo-reversible crosslinking network and an adjustable crosslinking degree. The resultant material exhibits alterable mechanical strength (varying from 0.16 MPa to 11.2 MPa) and a variable elastic modulus ( Y, from 0.6 MPa to about 79 MPa). Of significance is that PSiFGE-BMI possesses a high ε ′ (up to 7.6), high electromechanical sensitivity ( β, up to 11.8 MPa −1 ), and a high actuation area strain (9.3%@9.8 V μm −1 ). In addition, the homogenous DE exhibits excellent shape memory and shape reconfiguration behavior with a fixing ratio ( R f ) and recovery ratio ( R r ) of above 90%. This work provides a new strategy to prepare homogenous DEs with improved electromechanical performance and shape memory behavior, leading to promising application prospects in actuated devices.